STUDI EVALUASI DAMPAK PEMEKARAN DESA WONOKARTO TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA PEMEKARAN (STUDI KASUS DESA WONOASRI, DESA WONOSOBO DAN DESA WONOKARTO KECAMATAN NGADIROJO KABUPATEN PACITAN) - Khasanah, Siti Uswatun; Santosa, Edi; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2018)
Lawfully, an implementation of separated village is determined in the regent legal ofPacitan on 31, 2006 about village building of Wonosobo and Wonoasri of Ngadirjo at Pacitancity. Wonosobo and Wonoasri are derivation town from Wonokarto in which it has beendivided on three autonomous area, such us; Wonoasri, Wonosobo and WonokartoBasically separated area gives an opportunities for social Safety, which becomes oneof the aims of govermental existance. On the other hand, automatically it also facilitatesgovernment to increase an coordination effeciveness and management of village building.Based on the government regulation of 78, 2007 that unfoldment aims to develop aninfrastructure building.This research is done not only to undurstand the development of the villageinfrastructure building after it has been divided, to understand the positive and negativeeffects to infrastructure building, to understand the impeding factors to infrastructure villagebut also to know an effect evaluation success of separated village of Wonokarto forinfrastructure building in the unfoldment area—Wonoasri, Wonosobo and Wonokarto.The research method which uses here is mixed method integrating two approaches inall the process researches. Thera are three towns becoming a population and sample of thisresearch such us; Wonoasri, Wonosobo and Wonokarto and it utilizes an interview andqoesioner technique. There are 99 respondens; 36 communities of Wonoasri; 23 communitiesof Wonosobo; and 40 communities of Wonokarto. There are 9 informans who wereinterviewed; social figures and other comuunities.The result of this research shows the result of evaluation effect of separated village ofWonokarto influences to infrastructure building in the three separated viilages—Wonoasri,Wonosobo and Wonokarto. The obstacles of this iplementation are internal and externalfactors, the expends, the participation of govornment, geogaraphical factor and anothers.The recommendation that can be given is urgently an active role of government andcommunities in either the planning, implementation, or perputation of village infrastructure.Keywords: Separated village, infrastructure building